Варианты учета контактного взаимодействия в бандажных полках при расчетах собственных колебаний лопаточного венца методом конечных элементов - Круглий, Я. Д. (НТУ "ХПИ", 2015)
Приведены результаты вычислительных экспериментов по определению закономерностей влияния конечноэлементного моделирования контактного взаимодействия бандажных полок на спектр собственных частот колебаний лопаточных венцов рабочих колес турбин. Установлено, что независимо от условий эксплуатации двигателя и соотношения геометрических размеров лопаток способ моделирования не оказывает существенного влияния на собственные частоты колебаний.

This paper presents the computational investigation on the influence of the finite element simulation method of contact interaction between shrouds on the natural frequency spectrum of blade rows. In the simulation of blade rows we assumed their structural rotational symmetry. The problem is solved using the finite element method. Three approaches to taking into account the contact interaction between shrouds are considered: 1. Applying of the compatibility conditions of nodal displacements at the nodes where non-zero contact pressures are observed; 2. Development of elastic elements (the values of the stiffness coefficient correspond to those of the contact pressure at the corresponding nodes); 3. Combination of the first and second approaches.
Variants of the consideration of the contact interaction in the shrouds for the modal analysis of the turbine blading by finite element method
Keywords: турбины среднего давления; напряженно-деформированное состояние; КЭ; контактное взаимодействие; blade assembly; frequency; vibration